2010
DOI: 10.1016/j.phytochem.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrochalcones: Implication in resistance to oxidative stress and bioactivities against advanced glycation end-products and vasoconstriction

Abstract: Flavonoids are a group of polyphenol compounds with known antioxidant activities. Among them, dihydrochalcones are mainly found in apple leaves (Malus domestica). Glycosylated dihydrochalcones were previously found in large amounts in leaves of two genotypes of Malus with contrasting resistance to fire blight, a bacterial disease caused by Erwinia amylovora. In the present study we demonstrate that soluble polyphenol patterns comprised phloridzin alone or in combination with two additional dihydrochalcones, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 47 publications
0
63
0
1
Order By: Relevance
“…8 Do extrato etanólico das raízes foi isolada e identificada a naftoquinona tecomaquinona (1), 5 e do extrato etanólico das folhas foram isolados e identificados o monoterpeno carvacrol, 9 o flavonoide naringenina (4',5,7-tri-hidroxiflavanona, 2), 10 a mistura de 3',4',5,7-tetra-hidroxiflavanona (3) 11 e 4',5,7-tri-hidroxi-6-metoxiflavona (4) 11 e a mistura de 2'-O-glicopiranosil-3,4,4',6'-tetra-hidroxi-di-hidrochalcona (5) 12 e 2'-O-glicopiranosil-4,4',6'-tri-hidroxi-di-hidrochalcona (6) 13 , resumidos na Tabela 1, foram usados para deduzir as estruturas dos componentes da mistura como 2'-O-b-D-glicopiranosil-3,4,4',6'-tetra-hidroxi-di-hidrochalcona (5) e 2'-O-b-D-glicopiranosil-4,4',6'-tri-hidroxi-di-hidrochalcona (6). Os dados da Tabela 1 permitiram também estabelecer a correlação inequívoca dos deslocamentos dos átomos de hidrogênio e carbono das duas di-hidrochalconas (5 e 6).…”
Section: Resultsunclassified
“…8 Do extrato etanólico das raízes foi isolada e identificada a naftoquinona tecomaquinona (1), 5 e do extrato etanólico das folhas foram isolados e identificados o monoterpeno carvacrol, 9 o flavonoide naringenina (4',5,7-tri-hidroxiflavanona, 2), 10 a mistura de 3',4',5,7-tetra-hidroxiflavanona (3) 11 e 4',5,7-tri-hidroxi-6-metoxiflavona (4) 11 e a mistura de 2'-O-glicopiranosil-3,4,4',6'-tetra-hidroxi-di-hidrochalcona (5) 12 e 2'-O-glicopiranosil-4,4',6'-tri-hidroxi-di-hidrochalcona (6) 13 , resumidos na Tabela 1, foram usados para deduzir as estruturas dos componentes da mistura como 2'-O-b-D-glicopiranosil-3,4,4',6'-tetra-hidroxi-di-hidrochalcona (5) e 2'-O-b-D-glicopiranosil-4,4',6'-tri-hidroxi-di-hidrochalcona (6). Os dados da Tabela 1 permitiram também estabelecer a correlação inequívoca dos deslocamentos dos átomos de hidrogênio e carbono das duas di-hidrochalconas (5 e 6).…”
Section: Resultsunclassified
“…The anti-glycation capacity of numerous medicinal herbs and dietary plants was comparable with [59], or even stronger than that of aminoguanidine [42,60,[61][62][63]. Several studies have demonstrated that the anti-glycation activity correlates significantly with the phenolic content of the tested plant extracts [5,50,59,64,65].…”
Section: Polyphenolsmentioning
confidence: 94%
“…Among the known dihydrochalcones, phloridzin and its aglycone, phloretin, are simple forms [91] and their biosynthesis in Malus has been recently described [92]. Bernonville et al (2010), demonstrated the presence of phloridzin alone or in combination with two additional dihydrochalcones, identified as sieboldin and trilobatin [60]. Phloridzin was shown to inhibit glucose intestinal absorption and renal resorption, resulting in normalization of blood glucose and overall diminution of glycaemia in animal models [93].…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a phytoalexin that provides resistance to the pathogens-Venturia inaequalis and Erwinia amylovora [13,14]. Phloridzin can inhibit lipid peroxidation [15,16].…”
Section: Introductionmentioning
confidence: 99%